Application of high-quality nursing combined with drug therapy in lower respiratory tract infections and its effect on changes of serum IL-2 and TNF in patients: High-quality nursing combined with drug therapy in lower respiratory tract infections - Zhang, Xuejun; Yu, Xiaoyan (Progress in Nutrition, 2021)
In this study patients in the observation group were given high-quality care in combination with sparfloxacin and amikacin. The cough disappearance time, moist rales disappearance time, and fever symptom disappearance time were significantly shorter in the observation group than in the control group, and the differences were statistically significant. The application of high-quality nursing combined with drug therapy in lower respiratory tract infections can effectively alleviate clinical symptoms, shorten the length of hospital stay, improve the quality of life of patients, and help regulate the levels of serum IL-2 and TNF, and promote early recovery of patients.